Player and Team Performance in EverQuest II and Halo 3 - SHIM, Kyong Jin (Institutional Knowledge at Singapore Management University, 2011)
The market for video games has skyrocketed over the past decade. In the United States alone, the video game industry in 2009 generated almost US$20 billion in sales. Furthermore, according to Lenhart et al. (2008), an estimated 97% of the teenage population and 53% of the adult population are regular game players. Massively multiplayer online games (MMOGs) have become increasingly popular and amassed communities comprised of over 47 million subscribers by the year 2008. MMOGs are online spaces providing users with comprehensive virtual universes, each with its own unique context and mechanics. They range from the fantastical world of elves, dwarfs, and humans to space faring corporations and mirrors of our world. Large numbers of users interact and role-play via in-game mechanics.